Reported Hours of Sleep, Diabetes Prevalence and Glucose Control in Jamaican Adults: Analysis from the Jamaica Lifestyle Survey 2007-2008 - Chisa G. Cumberbatch; Novie O. Younger; Trevor S. Ferguson; Shelly R. McFarlane; Damian K. Francis; Rainford J. Wilks; Marshall K. Tulloch-Reid (International Journal of Endocrinology)
Background. There are limited data on sleep duration and diabetes from developing countries. We therefore examined the relationship between reported hours of sleep, diabetes prevalence and glucose control in Jamaican adults. Methods. Data on reported hours of sleep and diabetes (based on glucose measurement and medication use) from a national survey of 15–74-year-old Jamaicans were analyzed. Results. The 2,432 participants (31% M, Age 42±16 years, BMI 27.6±6.6 kg/m2, diabetes prevalence 12%) reported sleeping 8.2±1.8 hours. In men, sleeping less than 6 hours (OR (95% CI) = 2.65 (1.09–6.48)) or more than 10 hours (OR (95% CI) = 4.36 (1.56–12.19)) was associated with diabetes when adjusted for age, BMI, and family history of diabetes. In women sleeping less than 6 hours was associated with a reduced likelihood of diabetes after adjusting for the same confounders ((OR (95% CI) = 0.43 (0.23–0.78)). There was no significant association between sleep and glucose control. Conclusion. Insufficient and excessive sleep was associated with increased diabetes prevalence in Jamaican men but not women.